PREPARASI MANGAN OKSIDA HASIL PERTUKARAN KATION Mg 2+ DENGAN K-BIRNESSITE YANG DISINTESIS MENGGUNAKAN REDUKTOR MALTOSA - Anna Ridha Utami; Amir Awaluddin; Pepi Helza Yanti (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Todorokite is a naturally occurring manganese oxides having tunnelled structure (3x3) with pore size of 6,9 Å. This type of manganese oxide could be synthesized from birnessite precursor by reflux method. The exchangeable cation K + in interlayer of birnessite can be replaced with Mg 2+ ions to produce a Mg-birnessite, which then could be converted into todorokite through calcination. The products were then characterized by X-ray Powder Diffraction (XRD) to determine their phases, crystallinity and purity. Data from Absorption Atomic Spectroscopy (AAS) indicated that the 70,63% replacement of K + with Mg 2+ was achieved within contact time of 14 h. Analysis for todorokite have been done with different contact time of 18, 20 and 24 hours. The results of XRD showed that the main phases were birnessite with todorokite as minor product that was obtained at reaction time of 20 hours.